Lymphocyte-monocyte ratio at day 14 of first cisplatin-doxorubicin chemotherapy is associated with treatment outcome of pediatric patients with localized osteosarcoma - Jun Ah Lee; Hea Lin Oh; Dong Ho Kim; Jung Sub Lim (Korean Pediatric Society, 2019)
Purpose We aimed to determine the prognostic significance of lymphocyte counts and the lymphocytemonocyte ratio (LMR) in pediatric patients with osteosarcoma. Methods We retrospectively reviewed the medical records of 27 pediatric patients with localized extremity osteosarcoma, treated at the Korea Cancer Center Hospital between May 2002 and March 2016. Leukocyte counts and LMR before treatment and on day 14 (LMR14) of the first cisplatin-doxorubicin chemotherapy round were evaluated. Patients were dichotomized according to the median value of these parameters, and survival rates were compared. Results The median age of the 27 patients was 9.9 years (range, 3.2-14.1 years) and tumor sites were: distal femur (n=14), proximal humerus (n=7), proximal tibia (n=2), proximal fibula (n=2), and elsewhere (n=2). Patients were followed up on for a median of 76.4 months (range, 4.5-174.7 months), and 5-year overall (OS) and event-free survival (EFS) rates were 66.0%±9.8% and 60.9%±9.7%, respectively. Patients with a higher pretreatment lymphocyte count (≥2,320/μL) had better OS (90.9% vs. 46.2%, P=0.04) and EFS (83.9% vs. 38.5%, P=0.02). However, the day 14 lymphocyte count was not associated with survival. While no survival difference was observed between patients grouped according to pretreatment LMR (median value, 6.3), patients with a higher LMR14 (≥5) fared better than those with lower LMR14 (5-year OS: 83.3% vs. 46.3%, P=0.04). Conclusion Pretreatment lymphocyte count and LMR during chemotherapy had prognostic significance in pediatric osteosarcoma patients. Further studies involving larger cohorts are necessary to validate our findings.